New insights into HDV persistence: the role of interferon response and implications for upcoming novel therapies - Zhang, Zhenfeng; Urban, Stephan (Journal of hepatology, 2021)
Chronic hepatitis D (CHD), a global health problem, manifests as the most severe form of viral hepatitis. The causative agent, HDV, is the smallest known human virus; it replicates its circular single-stranded RNA genome in the nucleus of hepatocytes. HDV requires HBV-encoded envelope proteins for dissemination and de novo cell entry. However, HDV can also spread through cell division. Following entry into hepatocytes, replicative intermediates of HDV RNA are sensed by the pattern recognition receptor MDA5 (melanoma differentiation antigen 5) resulting in interferon (IFN)-β/λ induction. This IFN response strongly suppresses cell division-mediated spread of HDV genomes, however, it only marginally affects HDV RNA replication in already infected, resting hepatocytes. Monotherapy with IFN-α/λ shows efficacy but rarely results in HDV clearance. Recent molecular insights into key determinants of HDV persistence and the accelerated development of specifically acting antivirals that interfere with the replication cycle have revealed promising new therapeutic perspectives. In this review, we briefly summarise our knowledge on replication/persistence of HDV, the newly discovered HDV-like agents, and the interplay of HDV with the IFN response and its consequences for persistence. Finally, we discuss the possible role of IFNs in combination with upcoming therapies aimed at HDV cure.